Risk factor of pneumonia on toddler at puskesmas (public health center) I South Denpasar - Yudiastuti Kadek, Ethi; Ni Made, Dewianti (International Journal of Research in Medical Sciences, 2018)
Background: The death of toddler due to pneumonia is still high because its risk factor still exist and has not been managed properly. United Nations International Children’s Emergency Fund (UNICEF) states that in 2011 there was 1.3 million deaths of children below five years old (toddler) and 14% of the number was caused by pneumonia. Methods: The design for this research was case control with 27 cases and 27 controls. The case was toddlers who were diagnosed with pneumonia by doctor of public health center (hereafter Puskesmas), aged 0-59 months and were recorded in the ill toddler register from January 1, 2016 until December 31, 2016, meanwhile control was healthy toddlers who were invited to Puskesmas during the research. Data was collected through interview, observation and measurement using questionnaire. Univariate, bivariate, multivariate analyses were performed using Stata SE 12.1. Results: Bivariate analysis showed that two years of breastfeeding and ARI frequency, as the risk factors of pneumonia on toddler. From bivariate analysis, it was found that the risk factor which was proven to be significant and increased pneumonia on toddler was OR ARI with the value of 5.67 (95% CI:1.16-27.82). Conclusions: ARI frequency as the risk factor of pneumonia on toddler at Puskesmas I South Denpasar.